Improving The Critical Thinking Ability of Students to Solve Mathematical Task - Basri, Hasan; As,ari, Abdur Rahman (Universitas PGRI Madiun, 2018)
This study aims to describe students' critical thinking skills before and after the learning process. Analysis of critical thinking skills in this study based on components of critical thinking evaluation, inferences, explanations, and self-regulation. This type of research is descriptive research with a qualitative approach. The research subject consisted of 2 students with low critical thinking abilities based on task 1 given at the beginning of learning, besides that good communication was also one of the subject selection criteria. The results of the analysis showed that both research subjects SS and FT experienced an increase in their critical thinking abilities, this was evident from each indicator critical thinking evaluation, inferences, explanation, and self-regulation. In each indicator of critical thinking, the research subject is able to demonstrate the ability to do evaluation, inferences, explanation, and self-regulation, this is certainly very different from the initial conditions of research subjects where they have not been able to do evaluations, inferences, explanation well. One of the things that allows an increase in critical thinking skills is the subject of teaching and learning activities, namely by giving task that require students to practice their critical thinking skills.